A descriptive examination of the types of relationships formed between children with developmental disability and their closest peers in inclusive school settings. (March 2013) - Webster, Amanda A.; Carter, Mark
Abstract Background One of the most commonly cited rationales for inclusive education is to enable the development of quality relationships with typically developing peers. Relatively few researchers have examined the features of the range of relationships that children with developmental disability form in inclusive school settings. Method Interviews were conducted with 25 children with developmental disability, aged 5 and 12 years, their 3 closest peers, and parents and teachers to examine 6 types of relationships. Results Behaviours associated with general friendship and acquaintance were the most commonly reported. Few dyads reported high rates of behaviour associated with special treatment, helping, ignoring, or intimate best friend relationships. Conclusions The relationships of the majority of dyads were characterised by friendship or acceptance, but evidence of more intimate relationships was limited. An important direction for future research is the examination of ways to encourage more intimate relationships.